Standardized Mortality Ratios (SMRs) and Radon Exposure Analysis for Lung Cancer and All-Cause Mortality in Locorotondo, Southern Italy - Giovanni Maria Ferri; Luigi De Maria; Giuseppe Delvecchio; Antonio Caputi; Stefano Sole; Gianmarco Giannelli; Gianfranco Sifanno; Ilaria Maria Di Somma; Floriana Pentimone; Domenica Cavone; Angela Stufano; Piero Lovreglio; et al. (Medicina)
Background and Objectives: Radon is a known risk factor for lung cancer, and residential radon exposure is the leading cause of lung cancer in never smokers; however, in Italy, there is still a lack of public awareness regarding the risk caused by residential radon exposure. In this mortality study, which was carried out in an Italian Apulian town (Locorotondo) of the Bari province, we aimed to analyze lung cancer mortality and all-cause mortality in a population highly exposed to radon. Materials and Methods: The study period was 1998–2021. Local and Italian population and national mortality data were collected from the Italian National Institute of Statistics (ISTAT) website platform. Local mortality data were collected using copies of the Local Health Authority death certificates. Results: We identified 117 lung cancers in the studied period. The mortality data trends revealed a decrease in the all-causes standardized mortality ratios (SMRs), increases in the incidence rates of lung cancer and colorectal cancer in recent years, and a decrease in the incidence of noncancer diseases. We also found high SMRs for colorectal cancer until 2016 among older females. With respect to the cardio-circulatory system, only in 2014 did the male SMRs significantly influence the total SMR; after this period, a decreasing stable trend was observed. Conclusions: The natural balance of the population is decreasing, and mortality is decreasing for all causes. A future study will be needed to assess the associations between observed lung cancer cases and domestic radon exposure to drive radon mitigation and public health strategies.